The effect of tantalum addition on the corrosion behavior of W-xTa alloys in 1 M NaOH solution - Baral, Susil; Bhattarai, Jagadeesh (BIBECHANA, 2013)
The role of tantalum addition on the corrosion behavior of the sputter-deposited nanocrystalline and amorphous W-xTa (x=8-77) alloys was studied in 1 M NaOH solution open to air at 25°C using corrosion tests and electrochemical measurements. Tungsten and tantalum metals act synergistically in enhancing the corrosion resistant properties of the W-xTa alloys and hence addition of 23 at% or more tantalum to the alloys were found to be effective to lower the corrosion rate of the alloys than those of alloy-constituting tungsten and tantalum elements. The corrosion rates of the W-xTa alloys containing 23-77 at% tantalum are nearly two orders of magnitude lower than that of tungsten and even slightly lower than that of tantalum in 1 M NaOH. Addition of tantalum metal in W-xTa alloys is effective for ennoblement of the open circuit corrosion potential of the tungsten metal in 1 M NaOH solution 25°C. DOI: http://dx.doi.org/10.3126/bibechana.v10i0.8363 BIBECHANA 10 (2014) 1-8